Religion and the English Language - Wallace, Layne (Pharos Journal of Theology, 2024)
In an article he intended to be an update of George Orwell’s Politics and the English Language, Arthur Schlesinger writes, “It takes a certain fortitude to pretend to amend Orwell on this subject” (Schlesinger, 1974: 553). Yes, amending Orwell on the subject of English usage takes fortitude, perhaps even hubris. So, it will not be attempted here. No, this essay is not an update of Orwell’s essay; it is an application of it to the field of religion. The argument presented here is that religious writers often misuse the English language, resulting in a lack of clarity and beauty. Importantly, those who write about the source of all beauty should not do so in ugly prose. The subject of an article should affect the aesthetic nature of the prose. Ugly prose to describe God is a misuse of the English language. Misuse of the English language in religious thought is both a result of poor thinking and a cause of it. The remedy is to put Orwell’s rules for writing into practice among religious writers and speakers. This article presents an argument that directly follows Orwell's observations and applies them to the field of religious studies.